2012
DOI: 10.1021/mz3000804
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Network-Forming Triblock Copolymers Using Tapered Block Interfaces

Abstract: We report a strategy for generating novel dual-tapered poly(isoprene-b-isoprene/styrene-b-styrene-b-styrene/methyl methacrylate-b-methyl methacrylate) [P(I-IS-S-SM-M)] triblock copolymers that combines anionic polymerization, atom transfer radical polymerization (ATRP), and Huisgen 1,3-dipolar cycloaddition click chemistry. The tapered interfaces between blocks were synthesized via a semi-batch feed using programmable syringe pumps. This strategy allows us to manipulate the transition region between copolymer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 41 publications
1
50
1
Order By: Relevance
“…However, high‐molecular‐weight materials, which provide high ionic conductivity and mechanical strength in BCP systems, decrease the overall materials' processability. From the standpoint of reducing T ODT (increasing processability), recent efforts on tapered BCPs deserve attention . Manipulating the interfacial composition in BCP systems provides a way to decouple the segregation strength ( χ eff N ) between blocks from the copolymer molecular weight; thus, the T ODT can be controlled independently from the molecular weight .…”
Section: Challenges and Outlookmentioning
confidence: 99%
See 1 more Smart Citation
“…However, high‐molecular‐weight materials, which provide high ionic conductivity and mechanical strength in BCP systems, decrease the overall materials' processability. From the standpoint of reducing T ODT (increasing processability), recent efforts on tapered BCPs deserve attention . Manipulating the interfacial composition in BCP systems provides a way to decouple the segregation strength ( χ eff N ) between blocks from the copolymer molecular weight; thus, the T ODT can be controlled independently from the molecular weight .…”
Section: Challenges and Outlookmentioning
confidence: 99%
“…From the standpoint of reducing T ODT (increasing processability), recent efforts on tapered BCPs deserve attention. [129][130][131] Manipulating the interfacial composition in BCP systems provides a way to decouple the segregation strength (v eff N) between blocks from the copolymer molecular weight; thus, the T ODT can be controlled independently from the molecular weight. 132,133 Moreover, the effects of domain orientations on transport in a polymer electrolyte are notable.…”
Section: Challenges and Outlookmentioning
confidence: 99%
“…This tactic (albeit with single-component monomer streams) is employed regularly for synthesizing polymers with predetermined compositional profiles in tapered block copolymers and gradient copolymers. [22][23][24][70][71][72][73][74] Extension of these methods to multicomponent bio-oils would allow for the synthesis of renewable heteropolymers with precise compositions and properties, greatly enhancing the feasibility of numerous bio-oil-based plastics for commercialization.…”
Section: Compositional Profiles Of Heteropolymersmentioning
confidence: 99%
“…1. [25][26][27][28][29] This architecture differs from gradient copolymers, which have a graded compositional prole extending along the entire polymer chain. [30][31][32][33][34][35] Previous studies have demonstrated that manipulating the segment distribution in BP systems can decrease the effective segregation strength between blocks by reducing the effective c; in other words, the processing temperatures can be tuned independent of the chemical constituents and the molecular weight (i.e., mechanical properties) using tapered interfaces.…”
Section: Introductionmentioning
confidence: 99%